Security of Block Ciphers : From Algorithm Design to Hardware Implementation /: From Algorithm Design to Hardware Implementation. (2015) - Sakiyama, Kazuo, 1971-; Sasaki, Yu; Li, Yang, 1986 June 28
No abstract available